2000
DOI: 10.1038/sj.ejcn.1601084
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of black and green tea has no effect on inflammation, haemostasis and endothelial markers in smoking healthy individuals

Abstract: Obejective: Firstly, to study the effect of tea and tea polyphenols on cardiovascular risk indicators of the in¯ammatory system (IL6, IL1b and TNF-a, CRP), and on haemostasis and endothelial proteins with an acute phase behaviour (®brinogen, vWF, PAI-1, FVIIa and u-PA). Secondly, to study the relationship between plasma levels of antioxidants (a-tocopherol, b-carotene and vitamin C) and these acute-phase, cardiovascular risk indicators. Design: Randomized study. Subjects: Sixty-four smoking healthy volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…Four-week administration of black tea, green tea and green tea extracts had no effect on the inflammatory markers IL-6, IL-1b, TNFa, CRP and fibrinogen (47) . However, the same period of time was enough to show a reduction of P-selectin levels concomitantly with an increase of urinary 4-O-methyl gallic acid, following black tea supplementation (48) .…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 99%
“…Four-week administration of black tea, green tea and green tea extracts had no effect on the inflammatory markers IL-6, IL-1b, TNFa, CRP and fibrinogen (47) . However, the same period of time was enough to show a reduction of P-selectin levels concomitantly with an increase of urinary 4-O-methyl gallic acid, following black tea supplementation (48) .…”
Section: Anti-inflammatory Properties Of Flavonoidsmentioning
confidence: 99%
“…High-sensitivity C-reactive protein (CRP) is a marker of systemic inflammation produced by the liver and a powerful predictor of cardiovascular risk in healthy populations (Ridker et al, 2002;Yeh & Willerson, 2003). Dietary effects on markers of inflammatory processes have hardly been studied and are not yet established (de-Maat et al, 2000;Sierksma et al, 2002). N-3 fatty acids are suggested to have anti-inflammatory effects; they appear to reduce the production of inflammatory cytokines associated with several chronic diseases, such as rheumatoid arthritis (Kremer, 2000) and inflammatory bowel disease (Belluzzi, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…39 Few human studies have evaluated the effects of consumption of green tea on hemostasis. de Maat et al 40 reported that consuming green tea for 28 days had no effect on hemostasis in normal-weight healthy smokers. Further long-term experimental studies are required to confirm the potential role of green tea consumption on hemostasis in individuals with obesity, insulin resistance and diabetes.…”
Section: Effect Of Green Tea and Cocoa On Biomarkers Ks Stote Et Almentioning
confidence: 99%